2021
DOI: 10.1002/pmh.1522
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interaction between personality dysfunction and traits in the statistical prediction of physical aggression: Results from outpatient and community samples

Abstract: The Alternative Model for Personality Disorders (AMPD), included in the Diagnostic and Statistical Manual of Mental Disorders (5th ed.) and the World Health Organization's International Classification of Diseases (11th ed.; ICD-11) are, respectively, hybrid categorical-dimensional and dimensional frameworks for personality disorders (PDs). Both models emphasize personality dysfunction and personality traits. Previous studies investigating the links between the AMPD and ICD-11, and self-reported physical aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…The Personality Psychopathology 5 has a scale measuring aggression, and this scale is positively correlated ( r = .44) with an antagonism scale (Brown & Sellbom, 2023). In a sample of 227 outpatients diagnosed with personality disorder (Leclerc, Savard, Vachon, Faucher, et al, 2022), self-reported aggression was positively associated with facets of negative affectivity ( r = .19, emotional lability), not associated with facets of detachment, and positively associated with facets of antagonism ( r s ranging .29–.33), disinhibition ( r s ranging .18–.45), and psychoticism ( r s ranging .26–.34). In a sample of community and clinical participants, self-reports of physical aggression were also related to Criterion A personality dysfunction ( r s = .33) and PID-5 trait domains ( r s around .3; Leclerc, Savard, Vachon, Payant, et al, 2022).…”
Section: Conceptualizing Personality Dysfunctionmentioning
confidence: 99%
“…The Personality Psychopathology 5 has a scale measuring aggression, and this scale is positively correlated ( r = .44) with an antagonism scale (Brown & Sellbom, 2023). In a sample of 227 outpatients diagnosed with personality disorder (Leclerc, Savard, Vachon, Faucher, et al, 2022), self-reported aggression was positively associated with facets of negative affectivity ( r = .19, emotional lability), not associated with facets of detachment, and positively associated with facets of antagonism ( r s ranging .29–.33), disinhibition ( r s ranging .18–.45), and psychoticism ( r s ranging .26–.34). In a sample of community and clinical participants, self-reports of physical aggression were also related to Criterion A personality dysfunction ( r s = .33) and PID-5 trait domains ( r s around .3; Leclerc, Savard, Vachon, Payant, et al, 2022).…”
Section: Conceptualizing Personality Dysfunctionmentioning
confidence: 99%
“…Another question regarding the relation of the ICD-11 personality disorder model with eating pathology concerns potential interactive effects. Recent research suggests that personality dysfunction moderates associations of maladaptive traits with relevant behaviors and outcomes [ 40 , 41 ]. For example, trait-specific behaviors and thought patterns (e.g., rigid standards) may be indicative of more pronounced eating pathology in persons with high personality dysfunction (e.g., be problematic in the presence of identity and self-worth problems) but unproblematic in persons with low personality dysfunction (e.g., persons with stable self-worth).…”
Section: Introductionmentioning
confidence: 99%